2016
DOI: 10.1145/2955101
|View full text |Cite
|
Sign up to set email alerts
|

Updatable, Accurate, Diverse, and Scalable Recommendations for Interactive Applications

Abstract: Recommender systems form the backbone of many interactive systems. They incorporate user feedback to personalize the user experience typically via personalized recommendation lists. As users interact with a system, an increasing amount of data about a user's preferences becomes available, which can be leveraged for improving the systems' performance. Incorporating these new data into the underlying recommendation model is, however, not always straightforward. Many models used by recommender systems are computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 52 publications
0
58
0
Order By: Relevance
“…We include this algorithm because it provides good recommendation quality at a low computational cost. RP 3 β: A version of P 3 α proposed in [34]. Here, the outcomes of P 3 α are modified by dividing the similarities by each item's popularity raised to the power of a coefficient β.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…We include this algorithm because it provides good recommendation quality at a low computational cost. RP 3 β: A version of P 3 α proposed in [34]. Here, the outcomes of P 3 α are modified by dividing the similarities by each item's popularity raised to the power of a coefficient β.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…Following the results of Ferrari Dacrema et al (2018) we chose as collaborative model RP3beta (Paudel et al 2017) which demonstrated a very competitive recommendation quality at a very small computational cost, since it does not require ML. RP3beta is a graph-based algorithm which models a random walk between two sets of nodes, users and items.…”
Section: Collaborative Filtering Modelmentioning
confidence: 99%
“…every group member is satisfied by a certain number of items in their package. Notions of novelty and diversity in recommender systems, as well as measures to quantify them and methods to improve them have been described by various authors [1][2][3][4]6].…”
Section: Introductionmentioning
confidence: 99%